2017
DOI: 10.26525/jtfs2017.29.3.371379
|View full text |Cite
|
Sign up to set email alerts
|

Use of Visible and Near-Infrared Spectroscopy for Discrimination of Eucalypt Species by Examination of Solid Samples

Abstract: Eucalypt species have high importance in the forestry sector in Brazil. The wood has wide range of uses, including pulp, charcoal, plywood panels and treated boards. However, eucalypt species are hard to identify in lumber, which can cause problems in industrial use. So, the aim of this study was to combine visible and near-infrared spectroscopy to discriminate wood samples of two Corymbia spp. and five Eucalyptus spp. Visible spectroscopy was performed according to the CIELab standard. The data were analysed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 20 publications
0
6
0
Order By: Relevance
“…Thus, the need to use alternative characteristics that allow the correct identification of the wood is evident, such as those revealed through colorimetry, DNA and near-infrared spectroscopy (MORI et al, 2005;NUNES et al, 2009;OLIVEIRA et al, 2015). Therefore, the wood color is one of the most important macroscopic aspects for the species differentiation (MORI et al, 2005) and its potential has already been evaluated by several studies (NISGOSKI et al, 2017;GONÇALVES, 2001;SILVA et al, 2015, SILVA et al, 2017. Nevertheless, studies on colorimetry are still necessary to identify the particularities of each species based on characteristics such as growth rings, vessels, rays, parenchyma type, extractive content, among others MORINONIO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the need to use alternative characteristics that allow the correct identification of the wood is evident, such as those revealed through colorimetry, DNA and near-infrared spectroscopy (MORI et al, 2005;NUNES et al, 2009;OLIVEIRA et al, 2015). Therefore, the wood color is one of the most important macroscopic aspects for the species differentiation (MORI et al, 2005) and its potential has already been evaluated by several studies (NISGOSKI et al, 2017;GONÇALVES, 2001;SILVA et al, 2015, SILVA et al, 2017. Nevertheless, studies on colorimetry are still necessary to identify the particularities of each species based on characteristics such as growth rings, vessels, rays, parenchyma type, extractive content, among others MORINONIO, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Among the species (Figure 6A), original spectra of Muellera campestris was separated from the others, and this distinction was confirmed by the ellipse grouping, which was the result of light-yellow color of wood. In some eucalypt species, Nisgoski et al (2017) also found a distinction of samples in PCA of reflectance spectra in function of wood color.…”
Section: Principal Component Analysis (Pca)mentioning
confidence: 82%
“…Maderas-Cienc Tecnol 24(2022):16, 1-20 Ahead of Print: Accepted Authors Version 4 Thus, the use of colorimeters or spectrophotometers can be an alternative, since the evaluation is fast and needs little training. Some studies have shown the potential of this technique to evaluate wood modifications after thermal treatment (Cademartori et al 2013), to characterize Eucalyptus wood (Mori et al 2005), and to distinguish Eucalyptus and Pinus species (Nisgoski et al 2017;Amorim et al 2013) and Myrtaceae species (Vieira et al 2019b), among others. However, for adequate species discrimination, it is necessary to have a database that includes all heterogeneous characteristics of wood, since color is influenced by various factors, like radial position in the trunk and anatomical section evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…Colorimetric parameters also are influenced by natural degradation or thermal treatment of wood (Torres et al 2012, Cademartori et al 2013. The application of wood colorimetric parameters in species discrimination or grouping is scarce; some examples are the separation of eucalyptus (Martins et al 2015, Nisgoski et al 2017) and some tropical species in Brazil (Silva et al 2017). Zhao (2013) proposed a wood species classification using color surface data and related good results in intra and inter specific variations.…”
Section: Variation Of Color Among Sections Within Species Collected I...mentioning
confidence: 99%